Strategi Penguatan Kemitraan Eksternal dan Optimalisasi Potensi Internal Petani Bawang Merah: Pendekatan Analytic Hierarchy Process (AHP) Berdasarkan Modal Finansial, Human, dan Sosial di Komoditas Bawang Merah Probolinggo: Strengthening Partnership Strategies of Shallot Farmers in Probolinggo Based on Financial, Human, and Social Capital: An Analytic Hierarchy Process Approach - Fath, Sabil; Ardianto, Muhammad Rizki; Putritamara, Jaisy Aghniarahim (Fakultas Pertanian Universitas Brawijaya, 2025)
This study aims to formulate strategies for strengthening external partnerships and optimizing the internal potential of shallot farmers in Probolinggo Regency through the Analytic Hierarchy Process (AHP) approach, based on three key resources: financial, human, and social capital. The analysis was conducted in October 2024 at Raudlatul Muta’allimien Female Islamic Boarding School, which serves as a socio-economic institution supporting community-based shallot agribusiness development. Data were collected through Focus Group Discussions (FGDs) involving experts in agriculture, livestock, and economics, and analyzed manually using Microsoft Excel to determine the priority weights among aspects. The AHP results revealed that the strategic priorities are, respectively: (1) the quality and infrastructure of natural resources, (2) access to technology and information, (3) external partnership networks, and (4) human resource capacity. These findings indicate that strengthening environmental and technological foundations is essential for developing social and human capacity. This approach aligns with the Resource-Based View (RBV) theory, emphasizing the optimization of internal resources to achieve sustainable competitive advantage.